The Cutting Age Literature, from Romanticism to Victorian Age: A Study on Victor Hugo and Alfred Tennyson - Mashao, Elizabeth Thadeus (Indonesian Journal of English Language Studies (IJELS), 2018)
This study compares the features of poetry works of Victor Hugo from the Romantic Movement to those of Alfred Lord Tennyson from the Victorian Age of literature who lived in cutting age of the two periods of literature. These two ages experienced great expansion of industrial and agricultural revolutions, expansion of British as a super power nation with many colonies and the French revolution which to a great extent influenced the writings of these authors. Romanticism style of portraying themes of imagination, natural beauty and individual emotions over reasoning and sense of intellect influenced the poets of the age of Victorian literature though they still addressed the problems of the Victorian age. Both poets composed short and long poems, used description and sentimental styles, used nature metaphorically to create imagery and describe the emotions of appreciating beauty of the nature and reflecting peopleâ€™s struggle in different situations of life.Key words: Literature of the Romantic period, literature of the Victorian Age, Victor Hugo,Â Alfred Tennyson.Â